2017
DOI: 10.1007/s10620-017-4727-3
|View full text |Cite
|
Sign up to set email alerts
|

Tubercular Intestinal Strictures Show a Poor Response to Anti-Tuberculous Therapy

Abstract: Only one-fourth of ITB patients with strictures show resolution of stricture following ATT. The resolution of strictures is dependent on disease location, and majority of them exhibit symptoms pertaining to stricture even after ATT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 16 publications
0
21
1
3
Order By: Relevance
“…In this series, it was found that peritoneum was involved in around 46% while intestine was involved in around 36% of cases. This is different from other recent studies from northern India where intestine was the most common site [25], [27]. The response of peritoneal tuberculosis to ATT is very good as there was complete resolution in all the cases.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…In this series, it was found that peritoneum was involved in around 46% while intestine was involved in around 36% of cases. This is different from other recent studies from northern India where intestine was the most common site [25], [27]. The response of peritoneal tuberculosis to ATT is very good as there was complete resolution in all the cases.…”
Section: Discussioncontrasting
confidence: 95%
“…However the surgeries are conservative and show very good results. A recent study from AIIMS, Delhi has shown that around 40% of intestinal tuberculosis [ITB] had stricturing disease and only one-fourth of strictures show resolution following ATT [27]. The resolution of strictures is dependent on disease location, duration and severity of stricture.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study from AIIMS, Delhi has shown that around 40% of intestinal tuberculosis had stricturing disease and only one-fourth of strictures show resolution following AKT. 10 The resolution of stricture is dependent on disease location, duration and severity of stricture. The present series showed strictures in seven out of 24 confirmed patients with intestinal tuberculosis (28%).…”
Section: Drug Induced Hepatitis Discussionmentioning
confidence: 99%
“…Whether tuberculous strictures resolve with antitubercular treatment (ATT) or not is controversial. A few studies state that the symptoms abate, but strictures remain in most patients [ 3 4 ]. Patel and Yagnik suggested that most intestinal tuberculous lesions, including strictures, resolve with ATT, suggesting that strictures are inflammatory rather than fibrotic [ 5 ].…”
Section: Introductionmentioning
confidence: 99%